(3UdI GdNda HehUhd GdSdas - (3eMeO Hf eMeO Hf SdjeGf Hf GdaGSj Hf WGgQ GdShSj GdQhOGdj GdeZQHj,J (B1094 (3g` s ((3GdWGFa s)
(3ChdgG (B:s
(3HMeO Gddg CUOi eG Hjf GdSeGY hGdbQGAI hGdELGRI GdNGUI hGdYGeI s
(3BNQgG (B:s
(3SdSdI Jdbjfi GdPcQ Hbhdg (B: (3SHMGf QHc QH GdYdRI YeG jUac hSdGe Ydi GdeQSdjf s
(3HChdgG ELGRI HNW GdeDdas
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B221s
Keywords: (3GdJGQjNs